Prevailing leadership styles exhibited by administrative department heads and their association with overall organizational well-being - Hutaihet, Haider Hasan (Jurnal Ilmu Keolahragaan, 2025)
Background. As a professional in the field of university sports, the researcher observed that the interaction styles used between managers and activity coordinators lack a basis in scientific principles. Sometimes, a dictatorial approach is adopted, while on other occasions, a democratic leadership style is implemented; likewise, there are instances of authoritarian and permissive styles being used. The leadership style adopted by managers is influenced by many variables, including gender and institutional context. Therefore, it is difficult to ascertain which leadership style can be considered optimal. Objectives. The objectives of the research were to ascertain the prevailing leadership styles and organizational health of sports activities managers, and to explore the relationship between prevailing leadership styles and organizational health of sports activities managers. Methods. The researcher identified a study sample of 100 administrators involved in sports activities. The survey sample included 8 individuals, while the pre-test sample included 40 participants. The initial application trial sample also consisted of 40 individuals. In addition, the researcher developed two measurement tools, focusing on leadership styles and organizational health. then used statistical methodologies to extract research results, leading to several important conclusions, most notably. Results. Sports activity managers in Iraq demonstrate organizational health. Furthermore, these managers use two distinct types of leadership styles: traditional and social support. The dominant leadership style has a positive impact on managers' organizational health. Conclusion. The researcher proposed several conclusion, most notably: encouraging managers to adopt alternative leadership styles that may lead to superior results, enhancing managers' motivation to collaborate to achieve diverse goals, and calling for further studies that investigate variables not addressed in the current research, as well as applying these findings to different samples.